Gaya Bahasa dalam Konten di Media Sosial TikTok dr. Ayman Alatas Menurut Perspektif Gen Z - Susanti, Destia Aprillia (Universitas Negeri Surabaya, 2023)
Abstract This research aims to find out the use of language in social media content owned by dr. Ayman Alatas (@aymanalts). Social media is a tool/mediation used by individuals or groups (Party 1) to communicate or interact with third parties online and to join and share with third parties and the owner of the TikTok @aymanalts account. This study uses a qualitative research approach. Research data was collected using interview techniques and observations of documents and videos posted by the TikTok @aymanalts account. The data is then analyzed using a qualitative descriptive analysis technique. The conclusion of this research is the language used by dr. Ayman through his TikTok account @aymanalts is a relaxed, slang and non-formal language in discussing various different topics in a short, concise and clear manner. Such a style of language belongs to a variety of relaxed and familiar languages, which turns out to be very popular with Gen Z who are followers of the TikTok account @aymanalts. The use of these language variations is even one of the main reasons for Gen Z to follow and be interested in dr. Ayman TikTok Account. Dr. Ayman always uses a relaxed and familiar language style in explaining various medical or health terms to his followers. Apart from being able to facilitate the acceptance and understanding of followers, this is also the main attraction of Dr. Ayman TikTok account and contens. Keywords: TikTok, Language Style, Gen Z, Ayman Alatas